Chyle leakage after robotic and open pancreaticoduodenectomy. (14th February 2020) - Shyr, Bor‐Uei; Shyr, Bor‐Shiuan; Chen, Shih‐Chin; Shyr, Yi‐Ming; Wang, Shin‐E
Abstract: Background: Chyle leakage is a well‐known but poorly characterized complication after pancreaticoduodenectomy (PD). No study examined the chyle leakage after robotic PD (RPD). Methods: Data regarding chyle leakage were prospectively collected and analyzed from patients undergoing RPD or open PD (OPD). Results: The study included 118 RPD and 165 OPD. Overall chyle leakage rate was 12.0%, with 13.6% for RPD and 10.9% for OPD. Chyle leakage was eventually resolved in all patients through conservative treatment. The drainage volumes were significantly higher in chyle leakage group from postoperative days (PODs) 1‐7, with a median of 240 mL on POD 1 and POD 7, as compared to 160 mL on POD 1 and 70 mL on POD 7 for those without chyle leakage. The number of lymph nodes involved and resected and pancreatic head adenocarcinoma affected the risk of developing chyle leakage, whereas the surgical approach used (RPD or OPD) did not. Conclusions: Chyle leakage after PD is not rare, and it can eventually be resolved through conservative treatment. The extent and radicality of the surgery probably have a significant effect on the risk of developing chyle leakage, but the surgical approach used does not. Abstract : Highlight Chyle leakage is a well‐known but poorly characterized complication after pancreaticoduodenectomy, especially by the robotic approach. Shyr and colleagues report a chyle leakage rate of 13.6% for robotic and 10.9% for open pancreaticoduodenectomy. They conclude that the extent and radicality of the surgery significantly affect the risk of chyle leakage.